Common Atrium in Ellis Van-Creveld Syndrome - Kartika Apshanti; Irsad Andi Arso; Bambang Irawan (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2015)
Single atrium is a complete absence of atrial septum.1 It is often found in Ellis-van Creveld Syndrome. Ellis-van Creveld Syndrome is a chondral and ectodermal dysplasia that is characterized by short ribs, polydactyly, growth retardation and also ectodermal and heart defects. We report a male, 18 years old who came with worsening of dyspnea. At physical examination we found short stature, polydactyly, cardiomegaly, severe scoliosis, genu valgum and nail hypoplasia. Transthoracic echocardiography showed the complete absence of atrial septum with signs of pulmonary hypertension.Keywords: common atrium, Ellis-van Creveld Syndrome, polydactyly